2020
DOI: 10.1111/jphs.12339
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the clinical pharmacist on the use of inhalers among asthmatic patients in Alkarak region in the South of Jordan

Abstract: ObjectivesThe main aims of the study were to highlight the impact of clinical pharmacist in patient education on the correct use of inhalers, and its consequences on medication adherence, asthma control and clinical outcomes. Methods Pre-post-interventional study was conducted over two patient visits in Jordan at Alkarak Governmental Hospital. Inhaler technique evaluation was assessed at first and second visits. All patients received inhaler technique counselling service prior to second visit. Patient adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Pharmacists evaluated each step performed by the subject against the checklist, enabling the provision of structured feedback. The most common errors identified were immediate expiration after inhalation and not waiting between inhalations 29 . It was found that more errors were made by those who used two inhalers than by those using a single inhaler, and the number of errors was inversely related to asthma control 24 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pharmacists evaluated each step performed by the subject against the checklist, enabling the provision of structured feedback. The most common errors identified were immediate expiration after inhalation and not waiting between inhalations 29 . It was found that more errors were made by those who used two inhalers than by those using a single inhaler, and the number of errors was inversely related to asthma control 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Assessment and training of proper inhaler technique was a primary intervention in most of the studies reviewed 11–14,19–23,26,29–33 . This was noted as a facilitator for success, resulting in improved medicine adherence, enabling the study to gain positive momentum 12,20,22 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations